Barriers to Retail Competition and Prices : Evidence From Spain - Hoffmaister, Willy (IMF Working Papers; Working Paper ;, 2006)
Why do prices in Spain's regions fail to converge? The prime suspects for this puzzling result are differences in regional barriers to entry in retail distribution. This paper develops a Cournot-Nash model of imperfect competition to illustrate the effect of barriers on prices. A unique data set-derived from an extensive analysis of competition policies in Spain- provides evidence that barriers to entry increase regional prices. The evidence also suggests that, consistent with the model's predictions, barriers to entry raise prices up to a point, and thus indicate that barriers have a threshold effect on prices.